2018
DOI: 10.1002/jcp.26776
|View full text |Cite
|
Sign up to set email alerts
|

SEMA3B‐AS1‐inhibited osteogenic differentiation of human mesenchymal stem cells revealed by quantitative proteomics analysis

Abstract: Human mesenchymal stem cells (hMSCs) are fibroblastoid multipotent adult stem cells with capacities of differentiation into osteoblasts and chondrocytes and show great potential in new bone formation and bone repair‐related clinical settings, such as osteoporosis. Long noncoding RNAs (lncRNAs) have been demonstrated to play important roles in various biological processes. Here, we report an antisense lncRNA SEMA3B‐AS1 regulating hMSCs osteogenesis. SEMA3B‐AS1 is proximal to a member of the semaphorin family Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Previous studies mostly focused on individual osteogenic differentiation potential of the cells, rather than comparing and clarifying their osteogenic differentiation behavior 8,9,31,32 . To address this concern, comparative proteomics-based systems biology analysis was performed for dissecting the osteogenic differentiation behavior of cBM-MSCs and cDPSCs in vitro, since quantitative proteomics analysis has been proposed as a promising tool for comprehensively analyzing an osteogenic differentiation by many MSC-based osteogenic models 33,34 . Time-series analysis (day 0 vs. day 7 vs. day 14) of osteogenic differentiation behavior by cBM-MSCs and cDPSCs was conducted to thoroughly clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mostly focused on individual osteogenic differentiation potential of the cells, rather than comparing and clarifying their osteogenic differentiation behavior 8,9,31,32 . To address this concern, comparative proteomics-based systems biology analysis was performed for dissecting the osteogenic differentiation behavior of cBM-MSCs and cDPSCs in vitro, since quantitative proteomics analysis has been proposed as a promising tool for comprehensively analyzing an osteogenic differentiation by many MSC-based osteogenic models 33,34 . Time-series analysis (day 0 vs. day 7 vs. day 14) of osteogenic differentiation behavior by cBM-MSCs and cDPSCs was conducted to thoroughly clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved the polypeptide samples in 2% acetonitrile/0.1% formic acid and analyzed by Triple TOF 5600 plus mass spectrometer coupled with Eksigent nanoLC system (SCIEX, USA). The polypeptide solution was added to the C18 capture column [63,64]. All reported proteins were based on the following conditions: (1) at least one peptide confidence > 95% (unused Prot Score ≥1.3); (2) FDR < 1%.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…Zhong et al reported that SEAS1 decreased HCC cell proliferation and progression by suppressing miR-718 through upregulation of PTEN [ 25 ]. SEAS1 also acted as a tumor suppressor gene in ESCC [ 26 ], gastric cancer [ 27 ], and human mesenchymal stem cells [ 28 ]. However, very few reports are available on the expression of SEAS1 in TNBC.…”
Section: Discussionmentioning
confidence: 99%